2009
DOI: 10.1016/j.jada.2009.06.369
|View full text |Cite
|
Sign up to set email alerts
|

A Moderate Serving of High-Quality Protein Maximally Stimulates Skeletal Muscle Protein Synthesis in Young and Elderly Subjects

Abstract: Ingestion of sufficient dietary protein is a fundamental prerequisite for muscle protein synthesis and maintenance of muscle mass and function. The elderly are often at increased risk for protein-energy malnutrition, sarcopenia and a diminished quality of life. This study sought to compare changes in muscle protein synthesis and anabolic efficiency in response to a single moderate (113 g; 220 kcal; 30 g protein) or large serving (340 g; 660 kcal; 90 g protein) of 90% lean beef. Venous blood and vastus laterali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
258
4
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(302 citation statements)
references
References 28 publications
17
258
4
15
Order By: Relevance
“…Current RDAs for protein consumption for middle-aged and older adults (0.8 g/kg bodyweight) and following a usual care low-fat, low-calorie, moderate-protein diet appear inadequate for retention of skeletal muscle mass [39]. Studies suggest that the retention of skeletal muscle mass in middle-aged and older adults may require 1.2 g of protein per kilogram per day (or more) with regular daily meals containing 20-30 g of protein with 8-9 g of essential amino acids with meals distributed and consumed several times per day to optimize the stimulation of MPS [21,40,41].…”
Section: Muscle Protein Synthesis Anabolic Resistance and Improvingmentioning
confidence: 99%
See 2 more Smart Citations
“…Current RDAs for protein consumption for middle-aged and older adults (0.8 g/kg bodyweight) and following a usual care low-fat, low-calorie, moderate-protein diet appear inadequate for retention of skeletal muscle mass [39]. Studies suggest that the retention of skeletal muscle mass in middle-aged and older adults may require 1.2 g of protein per kilogram per day (or more) with regular daily meals containing 20-30 g of protein with 8-9 g of essential amino acids with meals distributed and consumed several times per day to optimize the stimulation of MPS [21,40,41].…”
Section: Muscle Protein Synthesis Anabolic Resistance and Improvingmentioning
confidence: 99%
“…However, even with 20 % kilocalorie from protein, this is likely inadequate to maintain lean body mass (e.g., 20 % protein, 1,350 kcal/day, 90 kg bodyweight, 0.75 g protein/kg, below the current RDA). Recent reviews, noted below, suggest that for middle-aged and older adults, RT may be optimized by consuming~1.2 g of protein per kilogram of bodyweight, 108 g of protein per day for a person weighing 90 kg, with 20-30 g of protein in several meals throughout the day [20,21]. Moreover, following usual energy restricted, lower to moderate protein diets and usual physical activity, cycles of weight loss and regain can result in a loss of lean body mass and additional gains in body fat in middle-aged and older adults, even for longer-term programs that effectively reduce weight and only show minimal weight regain [22,23].…”
Section: Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the subjectspecific protein doses distributed in connection with the resistance training is not known, studies utilizing protein seem to indicate a plateau in muscle protein synthesis from the ingestion bolus between 20-40 g of protein (12). Similarly, in a study conducted by Symons et al (13), 30 g of protein in the form of beef in a single meal resulted a maximum stimulation of skeletal muscle protein synthesis in both young and old subjects. A threefold increase in protein intake did not further stimulate protein synthesis.…”
Section: Dear Editormentioning
confidence: 96%
“…Recent suggestions are that older adults should consume 1·0-1·2 g/kg/d, although this is debated (259)(260)(261)(262)(263) . It has also been suggested that older people potentially divide protein intake during the day to consume 25-30 g high quality protein per meal in order to maximise protein synthesis (264,265) . At present, there is no recommendation for younger adults although the recommendation to consume 0·8 g/kg/d protein would appear to be wise.…”
Section: Population Advicementioning
confidence: 99%